Performance and Emission Analysis of Four-Stroke Diesel Engine Single Cylinder on Toroidal Piston Modification with B30 Fuel - Adhi Iswantoro; I Made Ariana; Bagus Gigih Luqmananto; M. Furqon Maulana; Semin Maulana (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Improvement of the performance of the diesel engine can be done by expanding the combustion chamber. One of the objectives of this research is to obtain optimal piston performance by modifying the piston crown to be 1mm deeper than the standard piston using B30 fuel. This research is also proof of previous research with a simulation that concluded that the performance of a diesel engine using a modified toroidal combustion chamber (TCC) +1mm piston has better performance than a standard piston. This research will analyze the comparison of the performance of a diesel engine using a standard piston and a modified piston on the diesel engine, using an experimental method with B30 biodiesel fuel with engine speed (RPM) variation of 1900 and 2100, also the dummy loads used are 1000, 2000, 3000, and 4000 Watts (W). From the results of the performance tests, it is concluded that the standard piston produces better performance than the modified piston with a very small difference in value in terms of torque, power, and SFOC. The level of NOx emissions produced by the standard RPM 1900 with 1000 W load is 1,483 g/KWh, at a load of 2000 W is 1,011 g/KWh, at a load of 3000 W is 1.375 g/KWh, at a load of 4000 W is 2,372 g/KWh, for standard piston RPM 2100 NOx emission levels produced at 1000 W load is 1,902 g/KWh, at 2000 W load is 1,450 g/KWh, at 3000 W load is 1.368 g/KWh, at 4000 W load is 1,066 g/KWh. The level of NOx emissions produced using a modified piston at 1900 RPM at 1000 W load is 1.865 g/KWh, at 2000 W load is 1.326 g/KWh, at 3000 W load is 1,250 g/KWh, at 4000 W load is 0.857 g/KWh, for RPM 2100 uses a modified piston at a 1000 W load is 1,970 g/KWh, at a 2000 W load is 1,583 g/KWh, at a 3000 W load is 1,465 g/KWh, at a 4000 W load is 1,226 g/KWh. NOx emission levels using standard pistons at RPM 1900 with B30 fuel tend to be smaller at low loads and larger at high loads compared to modified pistons, while NOx emission levels using standard pistons at RPM 2100 fueled by B30 are smaller than using a modified piston.